Innovative Fast Time Simulation Tools for Briefing / Debriefing in Advanced Ship Handling Simulator Training and Ship Operation - Benedict, Knud; Fischer, Sandro; Gluch, Michael; Kirchhoff, Matthias; Schaub, Michele; Baldauf, Michael; Müller, Burkhard (Transactions on Maritime Science, 2017)
The innovative “Simulation-Augmented Manoeuvring Design, Monitoring & Control” system (SAMMON) based on Fast Time Simulation (FTS) technology was developed at the Institute for Innovative Ship Simulation and Maritime Systems (ISSIMS) of the Maritime Simulation Centre Warnemuende MSCW. The system consists of software modules for (a) Manoeuvring Design & Planning, (b) Monitoring & Control based on Multiple Dynamic Prediction and (c) Trial & Training. It is based on complex ship dynamic models for rudder, thruster or engine manoeuvre simulation under different environmental conditions. It is an effective tool for lecturing and demonstrating ship's motion characteristics, as well as for ship handling simulator training. It allows the trainee to immediately see the results of the actual rudder, engine or thruster commands, without having to wait for the real-time response of the vessel. The Maritime Simulation Centre of AIDA Cruises at Rostock/Germany and the CSMART Center for Simulator Maritime Training of Carnival Corporation at Almere/NL have some experience with the use of this new technology to improve simulator training in Advanced Ship Handling Training courses. Examples of its application in briefing/debriefing and introductory lectures for simulator exercises specifically for typical cruise ships with Twin-Screw and Rudder systems will be presented in the paper and at the conference.